Influence of corn, Zea mays, phenological stages in Diatraea saccharalis F. (Lep. Crambidae) oviposition - More, Marcela (2003)
Diatraea saccharalis F. is a major pest to maize, sorghum and sugarcane crops in Latin America and the most damaging insect pest of maize in Argentina. Female moths lay their eggs on lower and upper sides of leaves and sheaths of corn plants. Oviposition behaviour of different species of corn stem borers is influenced by host plant phenology in different ways. Host pubescence affects oviposition behaviour in different species of caterpillars. Oviposition preferences for phenological stages, leaf surface and vertical distribution in corn plants were investigated. Corn plots of 120 m2 were sown with a Pioneer pubescent cultivar in six planting dates, each one replicated three times according to a completely randomized design. Throughout the season 14 samplings were carried out, during which plants were randomly chosen within each of the six treatments and exhaustively examined in order to count the number of egg masses and their location in the leaf surface and in the vertical structure of the plant. Diatraea saccharalis preferred laying their eggs on the lower sides of leaves located in the middle stratum of corn plants whose phenological stages were older than V10. Our study suggests that attention should be paid to the influence of crop phenological stage in the location of egg masses in futures studies, as oviposition preference can change through plant maturation.